Effectiveness of Professional Learning Communities in Ghanaian Basic Schools through the Lenses of Socio-Cultural Theory - Dandy George Dampson (Journal of Educational Issues, 2024)
This study employed the explanatory sequential mixed-methods design to assess the effectiveness of PLCs in Ghanaian basic schools. Using proportional stratified random sampling technique, the study selected 650 respondents (400 teachers and 250 headteachers) from the basic schools in five regions of Ghana for the quantitative phase of the study. Subsequently, 30 teachers and 10 headteachers from these schools were sampled purposely for the qualitative phase of the study. An adapted version of PLACA-R (6-dimensions; α = .84-.92) from Olivier and Hipp (2010) was used to collect quantitative data whilst researchers designed an interview guide was used to gather qualitative data. The quantitative data were analyzed using descriptive (means and standard deviation) statistics whilst the qualitative data were analyzed thematically. The study established the level of PLC activities in the basic schools is low on all the 6 dimensions of the scale except shared and supportive leadership. A good number of the basic schools have never held any PLC meetings since the curriculum was introduced. Schools that observed PLC meetings often ignore the delivery methods in the PLC manual. The study also found that female teachers practice PLC more than male teachers. The study further established that age, educational qualification and years of experience have a significant impact on the practice of PLC. The study concluded that teachers and headteachers in the basic schools lack knowledge and pedagogical skills about PLCs and their roles in the professional development of the teachers. It was recommended that the participation of PLCs by teachers and Headteachers should be used as one of the tools for teacher promotion.